2007
DOI: 10.1590/s1415-47572007000300024
|View full text |Cite
|
Sign up to set email alerts
|

Anticlastogenic potential and antioxidant effects of an aqueous extract of pulp from the pequi tree (Caryocar brasiliense Camb)

Abstract: The effectiveness of an aqueous extract of Caryocar brasiliense (Caryocaraceae) Camb pulp, popularly known in Brazil as pequi, against clastogenicity induced by cyclophosphamide and bleomycin was evaluated using an in vivo mouse bone marrow cell micronuclei test, an in vitro Chinese hamster ovary cell (CHO-K1) chromosome aberration test and an in vitro antioxidant assay based on the oxidative damage to 2-deoxy-D-ribose (2-DR) induced by hydroxyl radicals ( • OH) generated by the reaction between ascorbic acid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 36 publications
4
30
0
4
Order By: Relevance
“…High amounts of alimentary fiber and antioxidant compounds (phenolic acids and carotenoids) are present, mainly in the pulp (ALMEIDA et al, 1998;LIMA et al, 2007). These compounds give to the pequi antioxidant properties that have been shown in several studies (PAULA-JUNIOR et al, 2006;KHOURI et al, 2007;ROESLER et al, 2008).…”
Section: Resultsmentioning
confidence: 78%
“…High amounts of alimentary fiber and antioxidant compounds (phenolic acids and carotenoids) are present, mainly in the pulp (ALMEIDA et al, 1998;LIMA et al, 2007). These compounds give to the pequi antioxidant properties that have been shown in several studies (PAULA-JUNIOR et al, 2006;KHOURI et al, 2007;ROESLER et al, 2008).…”
Section: Resultsmentioning
confidence: 78%
“…Khouri et al (2007) and Miranda-Vilela et al (2008) suggested that C. brasiliense pulp, as chloroform or aqueous extract, has anticlastogenic and antimutagenic potentials, being able to inhibit cyclophosphamide (CP)-and bleomycin (BLM)-induced DNA damage in mice. They also demonstrated antiproliferative activity when tested in vitro in hamster cells, possibly due to its antioxidative properties (Khouri et al, 2007).…”
Section: Anticancer Activitymentioning
confidence: 99%
“…The impact of the use of this fruit on practical routine has already been demonstrated with the commonly used chemotherapeutic drugs such as bleomycin and cyclophosphamide, a well-known agent, which can cause oxidative damage to DNA [11,38] . This effect can be minimized by Pequi oil, probably due to the high concentrations of antioxidants present in the fruit [11,12] , thus reinforcing the known power of antioxidants to detoxify the cytotoxic metabolites of chemotherapy drugs [39] .…”
Section: Discussionmentioning
confidence: 99%
“…This effect can be minimized by Pequi oil, probably due to the high concentrations of antioxidants present in the fruit [11,12] , thus reinforcing the known power of antioxidants to detoxify the cytotoxic metabolites of chemotherapy drugs [39] . In addition, some fruits such as Pequi are a really good source of flavonoids.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation